2023
DOI: 10.1126/sciadv.add7856
|View full text |Cite
|
Sign up to set email alerts
|

Giant photon momentum locked THz emission in a centrosymmetric Dirac semimetal

Abstract: Strong second-order optical nonlinearities often require broken material centrosymmetry, thereby limiting the type and quality of materials used for nonlinear optical devices. Here, we report a giant and highly tunable terahertz (THz) emission from thin polycrystalline films of the centrosymmetric Dirac semimetal PtSe 2 . Our PtSe 2 THz emission is turned on at oblique incidence and locked to the photon momentum of the incident pump beam. Notably, we find an emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Note that the THz emission efficiency of our PtTe 2 films is three order magnitude larger than that of the standard ZnTe (Supplementary Fig. 13 and Supplementary Table 1 ), and it is comparable to those of topological semimetals 13 , 27 . The linear pump-fluence dependence of THz emission indicates that the emitted THz signals are dominated by a second-order nonlinear effect (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Note that the THz emission efficiency of our PtTe 2 films is three order magnitude larger than that of the standard ZnTe (Supplementary Fig. 13 and Supplementary Table 1 ), and it is comparable to those of topological semimetals 13 , 27 . The linear pump-fluence dependence of THz emission indicates that the emitted THz signals are dominated by a second-order nonlinear effect (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 81%
“…In this regard, polarized terahertz (THz) emission spectroscopy based on ultrafast femtosecond lasers is a powerful optical tool for generating and detecting ultrafast spin photocurrents 24 , 25 . Very recently, THz emission has been observed in centrosymmetric Dirac semimetal PtSe 2 films due to the photon drag effect 26 , 27 and a second nonlinearity from a structural asymmetry 28 . Remarkably, Luo et al 5 observed the light-induced transient phase transition and hence giant photocurrent (i.e., THz emission) in bulk Dirac semimetal ZrTe 5 .…”
Section: Introductionmentioning
confidence: 99%
“…51 These nonlinear optical effects are the primary cause of THz emission in single-layer (only NM layer) systems. 29,52 Because PtTe 2 has a centrosymmetric structure, it does not result in any THz emission under normal laser incidence, which is also evident in Figure 2b. Therefore, the polarization angle-dependent results shown in panels b and c of Figure 3 confirm that the entire THz emission from the PtTe 2 /Co-STE can be attributed to the SCC phenomena.…”
Section: T H Imentioning
confidence: 74%
“…Prior investigations of the nonlinear properties of PtSe2 have been restricted to PtSe2 as a saturable absorber with no demonstrations on the layer dependent nonlinearities 28 . Very recent studies have investigated THz photocurrents in PtSe2 but were limited to a single thickness of 2.4 nm 29 or 50 nm, 30 limiting the understanding of the effect of the bandstructure. Further, these studies have assumed an entirely centrosymmetric nature and neglected the effect of the substrate.…”
Section: Introductionmentioning
confidence: 99%